Evaluasi Alat Dosimeter untuk Penelitian Radionuklida pada Kedokteran Nuklir - Widianti, Lisa; Marta, Devi; Nur Lathiifa, Gusti Annisa; Putri, Erlinda Ratnasari (Progressive Physics Journal, 2025)
Radionuclides are widely used in nuclear medicine for diagnosis and therapy, but precise measurement of radiation dose is essential to keep patients and medical personnel safe. Dosimeters play a key role in measuring and evaluating radiation dose. This article discusses various types of dosimeters that are often used, such as Thermoluminescent Detectors (TLD), Optically Stimulated Luminescence Dosimeters (OSLD), and Radiochromic films (Gafchromic EBT3). The discussion covers how each device works, advantages, disadvantages, and performance. The review shows that each dosimeter has certain advantages: TLD is suitable for personal dose measurement, OSLD is effective for monitoring exposure in the work environment, and Gafchromic EBT3 helps visualise dose distribution in radiation therapy. The article also emphasises the need for innovation in dosimetry technology to improve accuracy, efficiency and safety. This review is expected to serve as a guide for researchers and practitioners in choosing the right dosimeter, while encouraging the development of better technologies to support safe and effective nuclear medicine.